2013
DOI: 10.5539/ijbm.v8n23p120
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Time Overruns in Public Construction Projects: The Case of Jordan

Abstract: Most construction projects in developing countries are characterized by overruns in time. This research was conducted in an attempt to identify major factors for such overruns in the typical developing environment of Jordan. A descriptive study was carried out and two types of data were collected. The overrun variables were extracted from the literature and from a thorough examination of the perception of 30 engineers, and then ranked according to their Severity Index (the product of Importance Index and Frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 25 publications
6
52
0
2
Order By: Relevance
“…Sweis, Rateb Sweis, Abu Rumman, Abu Hussein & Dahiyat, 2013). The causes and impacts of delay factors in construction industry not only vary from project to project but also from geographical location to another due several reasons including and not limited to the environmental, the topographical and the technological constraints (Sweis, 2013;Shebob, Dawood & Shah, 2012). Shebob et al (2012) mentioned in his study that in addition to country and projects variances in term of delay there is a certain projects are only a few days late while some projects are delayed by over a month or a year.…”
Section: Critical Delays Reviewmentioning
confidence: 99%
“…Sweis, Rateb Sweis, Abu Rumman, Abu Hussein & Dahiyat, 2013). The causes and impacts of delay factors in construction industry not only vary from project to project but also from geographical location to another due several reasons including and not limited to the environmental, the topographical and the technological constraints (Sweis, 2013;Shebob, Dawood & Shah, 2012). Shebob et al (2012) mentioned in his study that in addition to country and projects variances in term of delay there is a certain projects are only a few days late while some projects are delayed by over a month or a year.…”
Section: Critical Delays Reviewmentioning
confidence: 99%
“…Sweis (2008) [17] found that change orders from clients are considered one of the five major factors causing delays in the Jordanian construction industry. Moreover, Sweis (2013) [18] concluded that governmental delays and design changes are the major causes of time overruns in construction projects.…”
Section: Such Figures Highlight a Critical Issue Facing The Jordanianmentioning
confidence: 99%
“…Similarly, Alshdiefat (2013) [13] found that claims in construction projects have become normal and expected, with most building projects in Jordan suffering from cost overruns and A. Alshdiefat, Z. Aziz Journal of Building Construction and Planning Research delays in completion; according to the results of this research, change orders are the main cause of these claims. Sweis et al (2013) [14] also found that change orders in construction projects in Jordan are considered to be one of the major factors that cause cost overruns. Such findings highlight the negative impact of change orders, and especially cost overruns, on Jordanian construction projects.…”
mentioning
confidence: 99%
“…Cost is amongst the major issues throughout a project lifecycle and is considered as a key factor of project success in this universal. Cost overrun is determined as a major concern within the construction industry worldwide [9]. The transportation projects are the most significant projects that have faced cost overruns factors from time to time [10].…”
Section: Cost Overrunsmentioning
confidence: 99%